2010
DOI: 10.1111/j.1540-8159.2010.02693.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Capability of Left Atrial Size Measured by CT, TEE, and TTE for Recurrence of Atrial Fibrillation Following Radiofrequency Catheter Ablation

Abstract: LA dimensions and AF type are highly predictive of AF recurrence following RFCA. LAV by CT has significant predictive benefit over standard LADs in severely enlarged atria even after adjustment for AF type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 27 publications
4
49
0
1
Order By: Relevance
“…In contrast, invasive techniques for determining LA volume such as angiography and point-bypoint electroanatomic mapping result in an overestimation of LA size and left atrial volume [344]. Recently, perhaps not surprisingly, a series of studies have demonstrated that LA volume is one of the strongest predictors of outcome following AF ablation [341,[346][347][348][349].…”
Section: Assessment Of Left Atrial Volumementioning
confidence: 93%
See 1 more Smart Citation
“…In contrast, invasive techniques for determining LA volume such as angiography and point-bypoint electroanatomic mapping result in an overestimation of LA size and left atrial volume [344]. Recently, perhaps not surprisingly, a series of studies have demonstrated that LA volume is one of the strongest predictors of outcome following AF ablation [341,[346][347][348][349].…”
Section: Assessment Of Left Atrial Volumementioning
confidence: 93%
“…Perhaps the most widely employed approach is measurement of the end-systolic left atrial dimension (LAD) in the parasternal long axis view according to the American Society of Echocardiography guidelines [339]. Although this parameter is widely used clinically to determine the eligibility for AF ablation with LAD cutoffs of 5 or 5.5 cm, recent reports have demonstrated that this parameter correlates poorly with true left atrial volume, as assessed by CT imaging [340,341]. Alternative methods to assess left atrial volume include 3D echo [342], CT imaging, MRI [343], left atrial angiography [344], 3D electroanatomic mapping [344], and TEE [341].…”
Section: Assessment Of Left Atrial Volumementioning
confidence: 99%
“…One possible explanation is that our AF cohort used a strictly selected patient population that excluded those with structural heart disease, hypertension, obesity, and other commodities, thus controlling the possible confounding and interaction of these factors. In addition, differences in the methods used to measure LA size, 21 ablation strategy, and the length of follow-up period may also have a bearing on the ablation outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Abecasis et al reported that an LA volume of 145 mL on CT is a good cutoff value for prediction of AF recurrence [21]. Similarly, Parikh et al observed a dramatic increase in AF recurrence when the maximum LA volume was >130 mL as assessed by multi-slice CT [22]. Thus, CT may be a better tool for evaluating LA size; however, contrast-enhanced CT is contraindicated in patients with renal dysfunction or allergy and involves exposure to X-irradiation.…”
Section: Clinical Events and La Size Evaluated By Tte And Other Modalmentioning
confidence: 99%